Eosinophil-derived IL-13 promotes emphysema. Issue 5 (30th May 2019) - Doyle, Alfred D.; Mukherjee, Manali; LeSuer, William E.; Bittner, Tyler B.; Pasha, Saif M.; Frere, Justin J.; Neely, Joseph L.; Kloeber, Jake A.; Shim, Kelly P.; Ochkur, Sergei I.; Ho, Terence; Svenningsen, Sarah; et al.
The inflammatory responses in chronic airway diseases leading to emphysema are not fully defined. We hypothesised that lung eosinophilia contributes to airspace enlargement in a mouse model and to emphysema in patients with chronic obstructive pulmonary disease (COPD). A transgenic mouse model of chronic type 2 pulmonary inflammation (I5/hE2) was used to examine eosinophil-dependent mechanisms leading to airspace enlargement. Human sputum samples were collected for translational studies examining eosinophilia and matrix metalloprotease (MMP)-12 levels in patients with chronic airways disease. Airspace enlargement was identified in I5/hE2 mice and was dependent on eosinophils. Examination of I5/hE2 bronchoalveolar lavage identified elevated MMP-12, a mediator of emphysema. We showed, in vitro, that eosinophil-derived interleukin (IL)-13 promoted alveolar macrophage MMP-12 production. Airspace enlargement in I5/hE2 mice was dependent on MMP-12 and eosinophil-derived IL-4/13. Consistent with this, MMP-12 was elevated in patients with sputum eosinophilia and computed tomography evidence of emphysema, and also negatively correlated with forced expiratory volume in 1 s. A mouse model of chronic type 2 pulmonary inflammation exhibited airspace enlargement dependent on MMP-12 and eosinophil-derived IL-4/13. In chronic airways disease patients, lung eosinophilia was associated with elevated MMP-12 levels, which was a predictor of emphysema. These findings suggest an underappreciated mechanism by which eosinophils contribute to the pathologies associated with asthma and COPD. This study suggests that eosinophils may contribute to the emphysema observed in a subset of patients with chronic airways disease http://ow.ly/mBsz30nvDaG